Réponses

  • Omnes
  • Modérateur confirmé
2014-05-04T23:00:56+02:00
Salut,

E= (3x + 2)² +(3x + 2)( x+7)

1 : Développement/réduction


E= (3x + 2)² +(3x + 2)( x+7)
E = (9x² + 12x + 4) + (3x² + 21x + 2x + 14)
E = 9x² + 12x + 4 + 3x² + 23x +14
E = 12x² + 35x + 18

2: Factorisation ;


E= (3x + 2)² +(3x + 2)( x+7)
E = (3x+2)(3x+2) + (3x+2)(x+7)
E = (3x+2)[3x + 2 + x + 7]
E = (3x+2)(4x + 9)

3: E pour x = 1/2


E = (3x+2)(4x + 9)
E = (3*1/2 + 2)(4*1/2 + 9)
E = (3/2 + 2)(2 + 9)
E = (3/2 + 4/2) * 11
E = 7/2 * 11
E = 77/2

4:  E = 0


E = (3x+2)(4x + 9)

(3x+2)(4x + 9) = 0
3x + 2 = 0
3x = -2
x = -2/3

4x + 9 = 0
4x = -9
x = -9/4

Bonne soirée !